Forensic accounting I / Hari Ramulu Munusamy - Munusamy, Hari Ramulu (2003)
Forensic and investigative accounting is a relatively new and evolving discipline, with its primary growth in the last two to three decades. Its roots, however, are based on the principles, practices, and approaches that have been in place for some time. There is still flexibility as to the final makeup and application of the principles, practices, and approaches that will ultimately define the profession. This is the challenge to the imagination and creativity of the forensic accounting practitioner.